ANALISA USABILITY PADA APLIKASI HUMAN RESOURCE HIRA MENGGUNAKAN METODE SYSTEM USABILITY SCALE DAN USE QUESTIONNAIRE - Karista Kafka, Titania; Badrul, Mohammad (LPPM Universitas Putera Batam, 2024)
In facing the challenges of human resource management (HR) in a competitive business era, many organizations are adopting Human Resource Hira applications to support workforce management. This research was conducted to analyze Hira's usability using the System Usability Scale (SUS) and Use Questionnaire methods. The background to the problem involves user complaints regarding the quality of Hira, such as loading that takes quite a long time when logging in, locations that often have errors when checking in, the pay slip feature that often does not appear, etc. This research aims to identify Hira usability evaluations and provide recommendations for improvements. The results of usability analysis using SUS show a decent level of usability, with an average score of 51.09. Meanwhile the results of the USE Questionnaire also indicate a very good level of usability, with an average score of 91%. Thus, this research contributes to the understanding that Hira has a high level of usability, creates a satisfying user experience, and meets organizational operational needs. Improvement recommendations are not required based on the results of this positive usability evaluation.